COMPARISON OF HAEMORRHOIDECTOMY OUTCOMES USING LIGASURE SMALL JAW DEVICE VERSUS CONVENTIONAL MILLIGAN-MORGAN TECHNIQUE - SHAHEEN , U; SABIR , M; HUSSAIN , S; TAHIR , JA; AKHTAR, N; RASHEED, U (Biological and Clinical Sciences Research Journal, 2024)
Haemorrhoids are a common anorectal condition, affecting about 10% of the population. Hemorrhoidectomy remains the preferred treatment for grade III and IV haemorrhoids, with the Milligan-Morgan technique being the traditional method since 1937. Recently, the LigaSure vessel sealing system has emerged as a novel approach, utilizing bipolar electro-thermal technology for precise tissue sealing. Studies suggest LigaSure offers benefits such as reduced operating time, less intraoperative bleeding, lower postoperative pain, and shorter hospital stays. This study aims to compare postoperative pain, operative time and blood loss during the procedure between the LigaSure techniques and the Milligan-Morgan to optimize patient outcomes. Objective: To compare haemorrhoidectomy with Ligasure Small Jaw device versus conventional Milligan Morgan technique in terms of operation time, intra-operative blood loss and postoperative pain. Methods: 100 patients were included in this study. Patients were randomly assigned to 2 groups: Group A (Haemorrhoidectomy with Ligasure small jaw device) and Group B (Milligan Morgan Haemorrhoidectomy); 50 patients in each group. The data from both groups was recorded on a predesigned questionnaire and the required variables for the study i.e. VAS pain score, operative time and blood loss etc. were noted and the data was analyzed via SPSS version23.Results: The majority of patients were aged 50-59 years (45%), with a mean age of 46.01 ± 7.377 years. Males predominated (67%), and most patients had a healthy BMI (55%), with a mean BMI of 25.03 ± 3.1. Grade 4 hemorrhoids were more common (65%) than grade 3 (35%). Most patients experienced symptoms for 12-24 months (52%) and had an ASA score of 1 (79%). In Group A, the mean operative time was significantly shorter at 39.66 ± 6.46 minutes compared to 59.8 ± 14.04 minutes in Group B (p<0.001). Group A also had a shorter mean hospital stay (2.16 ± 0.911 days vs. 2.18 ± 1.043 days, p<0.001). Blood loss was significantly lower in Group A (51.04 ± 6.22 ml) compared to Group B (71.76 ± 9.8 ml, p<0.001). Pain scores on the day of surgery were lower in Group A (5.1 ± 0.57) than Group B (6.5 ± 0.50, p<0.001), a trend that continued on the 1st, 14th, and 28th postoperative days (p<0.001).Conclusion: Through our comprehensive analysis, we affirm that the Ligasure technique demonstrates superior outcomes in terms postoperative pain assessed via Visual Analog Scale (VAS), operative blood loss, duration of hospitalization, and operative time when compared to the Milligan-Morgan technique.